Crankshaft
By adjusting the chemical composition and surface structure of the crankshaft, ensuring that the surface hardness of the journal and pin is below HV450, the problem of insufficient bite resistance of the existing crankshaft is solved, and the crankshaft bite resistance is significantly improved.
Patent Information
- Application Number
- CN202180058495.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-28
- Filing Date
- 2021-09-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-09-24
AI Technical Summary
While improving fatigue strength and wear resistance, existing crankshafts are difficult to meet the improvement of low viscosity lubricating oil and fine shaft design requirements against bite resistance caused by the improvement of fuel efficiency in recent years.
By adjusting the chemical composition and surface structure of the crankshaft, the surface hardness of the shaft journal and pin is below HV450, and the tissue contains more than 80% by volume of tempered martensite, and the surface and tissue structure are optimized to improve bite resistance.
The crankshaft's bite resistance is significantly improved, which meets the requirements for bite resistance, while maintaining fatigue strength and wear resistance.
Smart Images

Figure CN116323992B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to crankshafts. Background Art
[0002] In order to improve fatigue strength and wear resistance, the crankshaft may be subjected to surface hardening treatment such as high-frequency quenching or nitrocarburizing.
[0003] Japanese Patent Publication No. 1-303309 discloses a method for manufacturing a crankshaft, in which a shaft portion, a bearing portion, a flywheel portion, a pin portion, and a crank arm portion are separately manufactured, welded together, and machined after quenching and tempering.
[0004] Japanese Patent Gazette No. 7-34134 discloses a surface treatment method for a crankshaft, in which a crankshaft made of non-tempered steel with a low carbon content is subjected to high-frequency quenching and tempering to a quenching hardness of HV400 to less than 500, and then surface plastic processing is performed to make the hardness of the surface hardened layer HV500 to 700.
[0005] Japanese Patent No. 4332070 discloses a high-strength steel for large forgings and a large crankshaft made of the steel. The publication describes heating the steel for forgings to 870°C, cooling (quenching) at a cooling rate of 20°C / min, and tempering at 580-630°C.
[0006] International Publication No. 2017 / 56896 discloses a rough crankshaft material, a nitrided crankshaft, and a method for manufacturing the same. The publication describes quenching at a temperature 10°C lower than the A3 point and tempering at a temperature of 550°C or higher and below the A1 point.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 1-303309
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 7-34134
[0011] Patent Document 3: Japanese Patent No. 4332070
[0012] Patent Document 4: International Publication No. 2017 / 56896 Summary of the invention
[0013] Problem that the invention aims to solve
[0014] Crankshafts are required to have not only fatigue strength and wear resistance, but also seizure resistance. In recent years, the lower viscosity of lubricating oils and the thinning of crankshaft sliding parts have been progressing in order to improve fuel efficiency, and crankshafts are required to have better seizure resistance.
[0015] An object of the present invention is to provide a crankshaft having excellent anti-seizure properties.
[0016] Solutions for solving problems
[0017] A crankshaft according to one embodiment of the present invention is a crankshaft comprising a journal portion and a pin portion, and its chemical composition is, by mass%, C: 0.35-0.40%, Si: 0.70% or less, Mn: 1.00-2.00%, Cr: 0.50% or less, Al: 0.050% or less, N: 0.020% or less, P: 0.020% or less, S: 0.005-0.200%, and the remainder is Fe and impurities, and the surface structure of each of the journal portion and the pin portion is a structure containing 80 volume % or more of tempered martensite, and the surface hardness is HV450 or less.
[0018] Effects of the Invention
[0019] According to the present invention, a crankshaft having excellent anti-seizure properties can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of a crankshaft according to an embodiment of the present invention.
[0021] Figure 2 This is a partial enlarged view of the journal and pin.
[0022] Figure 3 To show Figure 1 A flowchart of an example of a method for manufacturing a crankshaft.
[0023] Figure 4 This is a schematic diagram of the evaluation device used in the seizure test.
[0024] Figure 5 Schematic diagram of the time variation of the surface pressure applied to the test shaft.
[0025] Figure 6 It is a graph showing the relationship between the surface hardness and the seizure surface pressure.
[0026] Figure 7 It is a graph showing the relationship between the surface hardness and the seizure surface pressure. DETAILED DESCRIPTION
[0027] In order to improve the anti-seizure performance, it is said that the surface hardness of the soft material in the sliding parts needs to be increased. In the crankshaft, there are also examples of improving the anti-seizure performance by increasing the surface hardness of the bearing metal, which is a soft material. On the other hand, the relationship between the surface hardness of the pin and journal parts of the crankshaft, which are hard materials, and the anti-seizure performance has not been systematically studied so far.
[0028] It is generally believed that by increasing the surface hardness, wear resistance is improved and seizure resistance is also improved. However, according to the investigation of the present inventors, contrary to this expectation, the lower the surface hardness of the pin portion and the journal portion, the higher the seizure resistance.
[0029] The present invention is completed based on this understanding. The following is a detailed description of the embodiments of the present invention with reference to the accompanying drawings. The same or corresponding parts in the drawings are marked with the same reference numerals, and their descriptions are not repeated. The size ratios between the components shown in the drawings do not necessarily represent the actual size ratios.
[0030] [Crankshaft]
[0031] Figure 1 Schematic diagram of a crankshaft 10 according to an embodiment of the present invention. The crankshaft 10 includes a journal portion 11 , a pin portion 12 , and an arm portion 13 .
[0032] The journal portion 11 is connected to a cylinder block (not shown). The pin portion 12 is connected to a connecting rod (not shown). The arm portion 13 connects the journal portion 11 and the pin portion 12. The journal portion 11 and the pin portion 12 slide on bearings formed on the cylinder block and the connecting rod, respectively.
[0033] [Chemical composition]
[0034] The crankshaft 10 has the chemical composition described below. In the following description, "%" of the element content means mass %.
[0035] C: 0.35~0.40%
[0036] Carbon (C) increases the hardness of steel and contributes to improving fatigue strength. On the other hand, when the C content is too high, quenching crack resistance and machinability decrease. Therefore, the C content is 0.35 to 0.40%.
[0037] Si: 0.70% or less
[0038] Silicon (Si) deoxidizes steel. On the other hand, when the Si content is too high, the machinability decreases. Therefore, the Si content is 0.70% or less. The lower limit of the Si content is preferably 0.01%. The upper limit of the Si content is preferably 0.50%.
[0039] Mn: 1.00~2.00%
[0040] Manganese (Mn) improves the hardenability of steel. On the other hand, when the Mn content is too high, the machinability decreases. Therefore, the Mn content is 1.00 to 2.00%.
[0041] Cr: 0.50% or less
[0042] Chromium (Cr) improves the hardenability of steel. On the other hand, when the Cr content is too high, the machinability decreases. Therefore, the Cr content is 0.50% or less. The lower limit of the Cr content is preferably 0.01%, and more preferably 0.05%. The upper limit of the Cr content is preferably 0.30%.
[0043] Al: 0.050% or less
[0044] Aluminum (Al) deoxidizes steel. On the other hand, when the Al content is too high, the machinability decreases. Therefore, the Al content is 0.050% or less. The lower limit of the Al content is preferably 0.001%.
[0045] N: 0.020% or less
[0046] Nitrogen (N) is an impurity. N reduces the hot ductility of steel. Therefore, the N content is 0.020% or less. On the other hand, if the N content is excessively limited, the smelting cost increases. The lower limit of the N content is preferably 0.001%, and more preferably 0.005%.
[0047] P: 0.020% or less
[0048] Phosphorus (P) is an impurity. P reduces the quenching crack resistance of steel. Therefore, the P content is 0.020% or less.
[0049] S: 0.005~0.200%
[0050] Sulfur (S) forms MnS and improves the machinability of steel. On the other hand, when the S content is too high, the hot workability of steel decreases. Therefore, the S content is 0.005 to 0.200%.
[0051] The balance of the chemical composition of the crankshaft 10 is Fe and impurities. The impurities here refer to elements mixed from ores and scraps used as raw materials for steel, or elements mixed from the environment of the manufacturing process, etc.
[0052] [organize]
[0053] The surface structure of each of the journal portion 11 and the pin portion 12 is a structure containing 80 volume % or more of tempered martensite, and the surface hardness is HV450 or less. By setting the surface structure of the journal portion 11 and the pin portion 12 to a structure containing 80 volume % or more of tempered martensite and the surface hardness to HV450 or less, the seizure resistance is significantly improved.
[0054] In determining the surface structure of the journal portion 11 and the pin portion 12, cementite is treated as a structure independent of tempered martensite. The surface structure of the journal portion 11 and the pin portion 12 preferably contains 10% by volume or more of cementite. The volume ratio of cementite in the surface structure of the journal portion 11 and the pin portion 12 is preferably 12% by volume or more, and more preferably 15% by volume or more. Cementite is preferably finely dispersed in a granular form.
[0055] The hardness of the surface of the journal portion 11 and the pin portion 12 is measured in accordance with JIS Z 2244 (2009). The test force is set to 300 gf (2.942 N). The hardness of the surface of the journal portion 11 and the pin portion 12 is preferably HV400 or less, more preferably HV350 or less, further preferably HV300 or less, and further preferably HV250 or less. The lower limit of the hardness of the surface of the journal portion 11 and the pin portion 12 is not particularly set, and is, for example, HV180, and more preferably HV200.
[0056] The structures of the journal portion 11 and the pin portion 12 other than the surface structures are arbitrary. That is, the journal portion 11 and the pin portion 12 may be structures containing 80 volume % or more of tempered martensite up to the core, or may be structures containing 80 volume % or more of tempered martensite only on the surface or near the surface.
[0057] Similarly, the hardness of the journal portion 11 and the pin portion 12 other than the surface is arbitrary. That is, the journal portion 11 and the pin portion 12 may have a hardness of HV450 or less up to the core, or may have a hardness of HV450 or less only on the surface or near the surface.
[0058] Sliding characteristics such as anti-seizure are usually influenced by the characteristics of the outermost surface of the parts. Therefore, in each of the journal 11 and the pin 12, if the outermost surface structure is the above-mentioned structure and the outermost surface hardness is the above-mentioned hardness, the effect of improving anti-seizure can be obtained. However, in order to obtain the effect more stably, in each of the journal 11 and the pin 12, it is preferred that the region from the surface to a depth of 1.0 mm has the above-mentioned structure and hardness. It is more preferred that the region from the surface to a depth of 2.0 mm has the above-mentioned structure and hardness, and it is further preferred that the region from the surface to a depth of 3.0 mm has the above-mentioned structure and hardness.
[0059] The journal portion 11 and the pin portion 12 each have a surface roughness Ra of preferably 0.100 μm or less. The journal portion 11 and the pin portion 12 each have a surface roughness Ra of more preferably 0.080 μm or less, and further preferably 0.060 μm or less.
[0060] Figure 21 is a partial enlarged view of the journal portion 11 and the pin portion 12 of the crankshaft 10. The crankshaft 10 further includes a fillet portion 14 formed at the boundary between the journal portion 11 and the arm portion 13 and at the boundary between the pin portion 12 and the arm portion 13. In this specification, the fillet portion adjacent to the journal portion 11 and the fillet portion adjacent to the pin portion 12 are not distinguished, and both are referred to as the fillet portion 14. The fillet portion 14 is formed into a smooth shape to relieve stress concentration.
[0061] The fillet portion 14 is a portion to which the strongest stress is applied in the crankshaft 10. The fatigue characteristics of the crankshaft 10 are dominated by the influence of the fatigue strength of the fillet portion 14. In addition, bending fatigue, which is a problem in the crankshaft 10, is dominated by the influence of the characteristics of the surface layer of the part. Therefore, from the viewpoint of improving the fatigue strength of the crankshaft 10, it is preferable to increase the hardness of the surface layer of the fillet portion 14.
[0062] More specifically, from the viewpoint of improving the fatigue strength of the crankshaft 10, the hardness of the fillet portion 14 from the surface to a depth of 2 mm is preferably set to HV580 or higher. The hardness of the fillet portion 14 from the surface to a depth of 2 mm is further preferably HV600 or higher, and even more preferably HV650 or higher. The upper limit of the hardness of the fillet portion 14 from the surface to a depth of 2 mm is not particularly set, and is, for example, HV800.
[0063] Even in the case where the hardness of the fillet 14 is increased in order to improve the fatigue strength of the crankshaft 10, the hardness of the area deeper than 2.0 mm from the surface of the fillet 14 is arbitrary. That is, in the fillet 14, the hardness up to the core may be HV580 or more, or the hardness of only the area from the surface to the depth of 2 mm may be HV580 or more. However, in order to obtain the effect more stably, it is more preferable to set the hardness of the area from the surface to the depth of 3.0 mm to HV580 or more, HV600 or more, or HV650 or more, and it is further preferable to set the hardness of the area from the surface to the depth of 4.0 mm to HV580 or more, HV600 or more, or HV650 or more.
[0064] The hardness of the fillet portion 14 is obtained by collecting a sample with a cross section (longitudinal section) parallel to the axial direction of the crankshaft 10 as a measurement surface and measuring the measurement surface in accordance with JIS Z 2244 (2009). The test force is set to 300 gf (2.942 N).
[0065] The structure of the fillet portion 14 is arbitrary. However, in order to improve the fatigue strength of the crankshaft 10, the hardness of the surface layer of the fillet portion 14 is set to HV580 or higher, and the structure of the region is preferably a structure containing martensite. More specifically, the structure of the region is preferably a structure containing 80% by volume or more of martensite. The volume fraction of martensite in the region is more preferably 90% by volume or more, and further preferably 95% by volume or more.
[0066] The "martensite" (fresh martensite) here refers to martensite in a quenched state or martensite that has been tempered at a low temperature to remove strain, and is distinguished from "tempered martensite". "Martensite" and "tempered martensite" can be distinguished by observing the amount and dispersion state of precipitated metal carbides and cementite using a microscope or the like. In addition, when determining the structure of the surface layer of the fillet portion 14, cementite is treated as a structure independent of martensite.
[0067] The structure and hardness of the portion other than the journal portion 11 , the pin portion 12 and the fillet portion 14 (eg, the arm portion 13 ) are arbitrary.
[0068] [Crankshaft manufacturing method]
[0069] Next, an example of a method for manufacturing the crankshaft 10 will be described. The manufacturing method described below is merely an example, and does not limit the manufacturing method of the crankshaft 10 .
[0070] Figure 3 1 is a flowchart showing an example of a method for manufacturing a crankshaft 10. The manufacturing method includes a process for preparing a blank (step S1), a hot forging process (step S2), a heat treatment process (step S3), a machining process (step S4), a quenching process (step S5), a tempering process (step S6), and a finishing process (step S7). Each process will be described in detail below.
[0071] A billet of the crankshaft 10 is prepared (step S1). The billet is, for example, a steel bar. The billet can be produced, for example, by continuous casting or blooming of molten steel having a predetermined chemical composition.
[0072] The blank is hot forged into a rough shape of the crankshaft (step S2). Hot forging can also be divided into rough forging and finish forging.
[0073] The raw crankshaft produced by hot forging is subjected to heat treatment such as normalizing as required (step S3). The heat treatment step (step S3) is an optional step and can be omitted depending on the required characteristics of the crankshaft.
[0074] The rough product of the crankshaft is subjected to machining (step S4). The machining includes cutting, grinding, drilling, etc. Through this process, an intermediate product having a shape close to the final product is manufactured.
[0075] The intermediate product of the machined crankshaft is quenched (step S5). Specifically, after heating to a specified heating temperature, it is quenched. At this time, a high-frequency induction heating device can be used for local heating, or a heat treatment furnace can be used to heat the entire intermediate product. However, in the case of local heating, it is preferred to heat at least the journal portion 11, the pin portion 12 and the fillet portion 14. The quenching can also be implemented in multiple times. The heating temperature is preferably above the Ac3 point, and more preferably above 900°C.
[0076] At this time, it is preferred that the hardness of the surface layer of the fillet 14 is HV580 or more. The hardness of the surface layer of the fillet 14 can be adjusted according to the chemical composition of the blank and the cooling rate during quenching. Specifically, if the content of elements such as C that contribute to hardenability is increased, or the cooling rate is increased, the hardness of the surface layer of the fillet 14 becomes higher. It should be noted that, in the case where the hardness of the surface layer of the fillet 14 does not reach HV580 by quenching, plastic processing such as embossing rollers can also be implemented to increase the hardness of the surface layer of the fillet 14.
[0077] The intermediate product after quenching is tempered (step S6). Specifically, for example, it is kept at a temperature of 330 to 750°C for a specified time. Tempering is performed in a manner such that the surface hardness of the journal portion 11 and the pin portion 12 is less than HV450. The higher the heating temperature or the longer the holding time, the lower the hardness can be. When the heating temperature is lower than 330°C, it is sometimes difficult to sufficiently reduce the hardness. On the other hand, if the heating temperature is higher than 750°C, austenite is sometimes produced in the structure. This austenite transforms into re-quenched martensite and ferrite / pearlite during cooling, so the hardness is sometimes not sufficiently reduced. The heating temperature is preferably 550 to 650°C. The holding time is, for example, 10 to 120 minutes.
[0078] At this time, it is preferred to use a high-frequency induction heating device to heat the journal portion 11 and the pin portion 12, and try not to heat the fillet portion 14. The tempering can also be performed in multiple times. In this way, the journal portion 11 and the pin portion 12 can be softened, while the fillet portion 14 is not softened. The heating position can be adjusted according to the shape of the induction coil, the distance between the induction coil and the target part, the output frequency, etc.
[0079] It should be noted that quenching and tempering can be performed multiple times, and in addition to quenching and tempering, other heat treatments can also be performed. For example, in order to suppress quenching cracks, low-temperature tempering at a temperature that does not significantly affect the surface structure and hardness can be performed.
[0080] The intermediate product after tempering is subjected to finishing as needed (step S7). For example, the journal portion 11 and the pin portion 12 are ground and polished to adjust the surface shape. When finishing is performed, the surface roughness Ra is preferably 0.040 to 0.100 μm.
[0081] The above is a description of the structure of the crankshaft 10 according to one embodiment of the present invention and an example of a method for manufacturing the crankshaft 10. According to this embodiment, a crankshaft having excellent anti-seizure properties can be obtained.
[0082] Example
[0083] The present invention is described in more detail below by way of examples, but the present invention is not limited to these examples.
[0084] Steels having the chemical compositions shown in Table 1 were used as blanks to produce test shafts for galling tests, and the relationship between surface hardness and galling resistance was investigated.
[0085] [Table 1]
[0086] Table 1
[0087]
[0088] Specifically, after the blank is heated to 1250°C, it is processed into an outer diameter of 63mm and a length of 570mm by hot forging (forging end temperature 1075°C). After air cooling to room temperature, cutting and descaling are performed. Then, a high-frequency induction heating device is used to perform high-frequency quenching by heating to a temperature above the Ac3 point and then water cooling. The frequency is adjusted in such a way that the thickness of the quenching hardened layer becomes more than 3.0mm. Then, tempering is performed by heating at 620°C or 350°C for 90 minutes and then air cooling. As a finishing process, the test shaft is ground and polished in such a way that the surface roughness Ra becomes 0.040~0.100μm.
[0089] As a comparative example, a test shaft in which tempering was omitted was produced.
[0090] The produced test shaft was used to carry out a seizure test. The seizure test was carried out using a crank metal wear resistance seizure evaluation device manufactured by Kobelco Seisakusho Co., Ltd. A schematic diagram of the evaluation device 20 is shown in FIG. Figure 4 The test shaft TP was inserted into the plurality of bearings 21, and the test shaft TP was rotated at 8000 rpm by a motor (not shown) while supplying oil to the bearings 21. The metal of the bearing was an engine bearing (Al alloy) manufactured by Daiho Industry Co., Ltd. The lubricating oil was set to 0W-16 or 0W-8, and the oil supply temperature was set to 130°C.
[0091] In this state, one of the bearings 21 is pulled down to increase the surface pressure applied to the test shaft TP in stages, and the test shaft TP is operated until seizure occurs. Figure 5 The time variation of the surface pressure applied to the test shaft TP is schematically shown in FIG. The holding time at the same surface pressure is 3 minutes, and the surface pressure increase amplitude at each stage is set to 4.0 MPa. When the surface temperature of the bearing becomes higher than the specified value, or the torque received by the test bearing becomes higher than the specified value, it is determined that seizure has occurred.
[0092] Tables 2 and 3 show the surface hardness, surface structure, surface roughness Ra, tempering conditions, seizure surface pressure, tempering conditions, etc. of each test shaft.
[0093] [Table 2]
[0094] Table 2
[0095]
[0096] [Table 3]
[0097] Table 3
[0098]
[0099] The column "Structure (volume %) from the surface to 3.0 mm" in Tables 2 and 3 records the main structure (the structure with the largest volume ratio) at the position from the surface to a depth of 3.0 mm. The value in parentheses is the volume ratio of the structure. Specifically, a section (longitudinal section) parallel to the axial direction of the test axis is used as the observation surface, and a field of view of 36 μm × 48 μm is observed at a depth from the surface to 3.0 mm, and the area ratio in the section is regarded as the volume ratio. The surface structures of the test axes No. 1 to 9 and No. 21 to 24 are all structures containing more than 80 volume % of tempered martensite.
[0100] Figure 6 and Figure 7 The relationship between the surface hardness and the seizure surface pressure is shown based on the data of the lubricating oil 0W-16. Figure 6 Involving steel A, Figure 7 Involving steel B. Figure 6 and Figure 7 As shown, the test shaft with a surface hardness of HV450 or less has a higher surface seizure pressure than the test shaft of the comparative example, showing excellent seizure resistance. In addition, although there is a deviation, it can be seen that the lower the surface hardness, the higher the seizure surface pressure.
[0101] One embodiment of the present invention has been described above, but the above embodiment is only an example for implementing the present invention. Therefore, the present invention is not limited to the above embodiment, and the above embodiment can be appropriately modified and implemented within the scope of the gist thereof.
[0102] Description of Reference Numerals
[0103] 10 Crankshaft
[0104] 11 Shaft neck
[0105] 12. Sales Department
[0106] 13 Arm
[0107] 14 Rounded corners.
Claims
1. A crankshaft comprising a journal portion and a pin portion, Its chemical composition is calculated by mass % as follows: C: 0.35-0.40%, Si: 0.70% or less, Mn: 1.00~2.00%, Cr: 0.50% or less, Al: 0.050% or less, N: 0.020% or less, P: 0.020% or less, S:0.005~0.200%、 Balance: Fe and impurities, The surface structure of each of the journal portion and the pin portion is a structure containing 80 volume % or more of tempered martensite, and the surface hardness is HV450 or less.
2. The crankshaft according to claim 1, further comprising a rounded corner portion, The rounded corner portion has a hardness of HV580 or more from the surface to a depth of 2.0 mm.
3. The crankshaft according to claim 2, wherein: The structure of the fillet portion from the surface to a depth of 2.0 mm is a structure containing 80 volume % or more of martensite.
4. The crankshaft according to any one of claims 1 to 3, wherein: The hardness of each surface of the journal portion and the pin portion is HV250 or less.
5. The crankshaft according to any one of claims 1 to 3, wherein: The structures of the surfaces of the journal portion and the pin portion further include 10 volume % or more of cementite.
6. The crankshaft according to any one of claims 1 to 3, wherein: The journal portion and the pin portion each have a surface roughness Ra of 0.100 μm or less.
Citation Information
Patent Citations
Manufacture of crank shaft
JP1989303309A
Surface treatment of crank shaft
JP1995034134A
Preform for crankshaft, nitride crankshaft, and manufacturing method for same
WO2017056896A1
High-strength thin steel sheet and manufacturing method therefor
JP2006070328A
Crank shaft and manufacturing method therefor
JP2017110247A